Short Latency Period of Radiation Induced Meningioma in Adult Patient Following High Dose Irradiation: A Case Report - Wicaksana, Aditya; Manusubroto, Wiryawan; Tamba, Daniel Agriva; Pangaribuan, Vega (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Introduction: We present a case of adult onset Radiation-Induced Meningioma (RIM) following resection of astrocytoma with short latency period of only 18 months. Case Report: A 44-year old man who had high dose irradiation following astrocytoma resection came to our institution due to the appearance of intracranial tumor in the field of radiation in the follow-up MRI. Observation was done and a head CT scan was done 6 months later, where intracranial tumor was doubled in size. Surgical resection was done and histopathological result of high-grade meningioma confirming the diagnosis of RIM. Most RIM are usually presenting in children receiving high dose radiotherapy with mean latency period of 26.2 ± 9.3 years. Result: Our patient is older at presentation; he underwent astrocytoma resection previously and was receiving high dose irradiation of 46 Gy. Conclusion: In astrocytoma patients receiving adjuvant radiotherapy, physician must be aware of RIM; in addition to the recurrence of the high-grade gliomas.